2017
DOI: 10.1113/jp274066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perinatal exposure to sucrose or high fructose corn syrup (HFCS‐55) on adiposity and hepatic lipid composition in rat offspring

Abstract: Key pointsr Fructose-containing sugars, including sucrose and high fructose corn syrup (HFCS), have been implicated in the epidemics of obesity and type 2 diabetes.r Few studies have evaluated the impact of perinatal exposure to these sugars on metabolic and physiological outcomes in the offspring.r Using a rat model, offspring exposed to a maternal sucrose or HFCS diet during the prenatal and/or suckling periods were found to have altered adiposity and liver fat content and composition at weaning.r Plasma lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 59 publications
1
47
0
1
Order By: Relevance
“…Unexpectedly, fructose-exposed male offspring showed decreased triglyceride levels compare to the control group. As described previously, the metabolic changes observed in fructose-exposed rats are quite conflicting among the studies, possibly due to study design (de Moura et al, 2009;Toop et al, 2015Toop et al, , 2017Yuruk and Nergiz-Unal, 2017).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Unexpectedly, fructose-exposed male offspring showed decreased triglyceride levels compare to the control group. As described previously, the metabolic changes observed in fructose-exposed rats are quite conflicting among the studies, possibly due to study design (de Moura et al, 2009;Toop et al, 2015Toop et al, , 2017Yuruk and Nergiz-Unal, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Unexpectedly, fructose‐exposed male offspring showed decreased triglyceride levels compare to the control group. As described previously, the metabolic changes observed in fructose‐exposed rats are quite conflicting among the studies, possibly due to study design (de Moura et al, 2009; Toop et al, 2015, 2017; Yuruk and Nergiz‐Unal, 2017). The discrepancies between the studies may be explained by differences in the amount (10%–60%) and route (diet, oral administration or drinking water) of maternal fructose intake, strain of rats (Wistar or Sprague–Dawley), the timing of exposure (prenatal or suckling periods) and the age at which offspring were assessed (immediately after weaning or later).…”
Section: Discussionmentioning
confidence: 93%
“…In this issue of The Journal of Physiology , Toop et al . () report that perinatal exposure (before birth and during lactation) to maternal consumption of sucrose or high fructose corn syrup (HFCS; 55% fructose) has detrimental effects on the offspring, chiefly on adiposity, plasma FFAs, hepatic fat content and hepatic lipid composition, which differed somewhat depending on the sugar and the window of exposure. The major changes are summarized in Fig.…”
Section: Maternal Fructose Consumption During Pregnancy and Lactationmentioning
confidence: 99%
“…For instance, offspring fed 70% of total calories as sucrose had a higher adiponectin concentration, and offspring fed 5% sucrose for 10 weeks presented with increases in adipocyte size and the adiposity index. However, other studies have revealed that affected offspring exhibit adaptive responses to abnormal prenatal exposures . The relationship between prenatal and postnatal high sucrose exposure and the possible mechanisms underlying this relationship are unclear.…”
Section: Introductionmentioning
confidence: 98%